Medication Beliefs in Patients Following Percutaneous Coronary Intervention: A Cross-sectional Study - Prima Agustia Nova; Ching-Huey Chen (Jurnal Keperawatan Indonesia, 2019)
Patients post percutaneous coronary intervention need to take medication for their health. Beliefs about medication influence patients’ adherence in taking their medication regimens. Therefore, the study aimed to identify medication beliefs in patients following percutaneous coronary intervention in Indonesia. This research used a cross-sectional study with the convenience sampling method. A total of 132 adult patients following Percutaneous Coronary Intervention participated in this study. This study used The Beliefs about Medicines Questionnaire to identify patients’ beliefs about medication. The majority of respondents were male (85.6%) with a mean age of 60 years. Beliefs about general overuse were found to be the highest among other categories; specific-necessity, specific concern, and general harm. Elucidating patients’ beliefs about the medication will provide health care providers with a better understanding of patient medication behaviors after percutaneous coronary intervention. Recognition of patients’ beliefs may aid in targeting specific intervention programs to improve patients’ adherence to medication following Percutaneous Coronary Intervention procedure.Abstrak Keyakinan Pengobatan pada Pasien yang Menjalani Intervensi Coronary Percutaneous: A Cross-Sectional Study. Pasien pasca intervensi koroner perkutan atau percutaneous coronary intervention (PCI) perlu minum obat untuk kesehatannya. Keyakinan terhadap pengobatan berpengaruh pada kepatuhan pasien dalam menjalani rejimen pengobatan. Penelitian ini bertujuan untuk mengidentifikasi keyakinan pengobatan pada pasien yang mengikuti PCI di Indonesia. Penelitian ini menggunakan studi cross-sectional dengan metode convenience sampling. Sebanyak 132 pasien dewasa yang menjalani prosedur PCI berpartisipasi dalam penelitian ini. Penelitian ini menggunakan The Beliefs about Medicines Questionnaire untuk mengidentifikasi keyakinan pasien tentang pengobatan. Mayoritas responden adalah laki-laki (85,6%) dengan usia rata-rata 60 tahun. Keyakinan tentang penggunaan berlebihan secara umum ditemukan sebagai yang tertinggi di antara kategori lainnya yaitu kebutuhan-spesifik, perhatian khusus, dan bahaya umum. Informasi mengenai keyakinan pasien tentang pengobatan akan memberikan pemahaman yang lebih baik bagi penyedia layanan kesehatan tentang perilaku pengobatan pasien setelah prosedur PCI. Pengakuan keyakinan pasien dapat membantu dalam menargetkan program intervensi khusus untuk meningkatkan kepatuhan pasien terhadap pengobatan setelah prosedur PCI. Kata Kunci: keyakinan pengobatan, percutaneous coronary intervention (PCI)